Fighting Over-Indebtedness: An Artificial Intelligence Approach: An Abstract - Ferreira, Mário (2022)
Ferreira, M. et al. (2022). Fighting Over-Indebtedness: An Artificial Intelligence Approach: An Abstract. In: Pantoja, F., Wu, S. (eds) From Micro to Macro: Dealing with Uncertainties in the Global Marketplace. AMSAC 2020. Developments in Marketing Science: Proceedings of the Academy of Marketing Science. Springer, Cham. https://doi.org/10.1007/978-3-030-89883-0_158